Investigation of Parvovirus B19 in Hashimoto thyroiditis - Hlail, Marwa Naeem; Mohammed, Ahmed Hasan (University of Thi-Qar Journal of Science, 2022)
Thyroiditis is a broad term that refers to a variety of clinical conditions marked by inflammation and damage to thyroid cells. These disorders could be caused by due to factors, including radiation, a microbial infection, or be linked to autoimmune thyroid disease, such as in Hashimoto thyroiditis (HT). This cross-sectional study aimed to the detection of anti-TPO antibodies and to investigate (Parvovirus B19) IgM and IgG antibodies in serum of patients to investigate their role in the pathogenesis of thyroiditis. The study included 91 patients suffering from thyroid dysfunction and diagnosed by performing of the thyroid hormone tests (FT3, FT4 and TSH) by Snibe Maglumi-800 Chemiluminescence Immunoassay, where they were divided into three groups namely (subclinical thyroiditis, hypothyroidism and hyperthyroidism). Then Moreover, the study investigates the determination which of them has HT by the detection of thyroid autoantibodies anti-TPO Ab and the detection of antibodies to specific (Parvovirus B19) IgM and IgG in the sera of patients by ELISA. The results of serology showed that the percentage of anti-TPO antibodies in the three investigated groups was (54.94%), and the highest percentage was in the hypothyroidism group, which amounted to (71.40%). The serological diagnosis also showed that the presence of antibodies to (Parvovirus B19) IgM was (90.10%) while, IgG levels were (100%) respectively. Conclusions: Parvovirus B19 infection is commonly seen in patients with thyroiditis.